The development of a recognition geometry algorithm for hybrid-subtractive and additive manufacturing - Homar, David (Strojniški vestnik, 2017)
In the last decade additive manufacturing of metal components has experienced enormous development. One of the most important achievements in this sector is the fact that nowadays it is possible to produce fully dense metal parts. Generally, additive manufacturing technologies are able to produce very complex geometries but are time and cost consuming for manufacturing of massive components. Machining technology, on the other hand, has the opposite characteristics. Both technologies, additive and subtractive, have advantages and disadvantages depending on the amount of material that need to be added or subtracted. The combination of these two technologies (i.e. hybrid manufacturing) results in a process where advantages of both technologies can be expected (cost, material consumption, etc.). Thus a novelty, the paper presents a development and analysis of software that analyzes the CAD model with geometry of the model and declares which part of model will be manufactured with machining and which will be produced by additive manufacturing. The software is evaluated on an industrial case from the field of injection mould inserts. Results show that such an automated algorithm decreases cost, better efficiency and nevertheless offer possibility to implement technology in industrial environment to improve manufacturing processes, i.e. in current case injection moulding process/technology.
Keywords: hibridna izdelava; konformni hladilni kanali; odrezovanje; tehnologije dodajanja materiala; tehnologije odvzemanja materiala